2008
DOI: 10.1080/10635150802426473
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study in Ancestral Range Reconstruction Methods: Retracing the Uncertain Histories of Insular Lineages

Abstract: Island systems have long been useful models for understanding lineage diversification in a geographic context, especially pertaining to the importance of dispersal in the origin of new clades. Here we use a well-resolved phylogeny of the flowering plant genus Cyrtandra (Gesneriaceae) from the Pacific Islands to compare four methods of inferring ancestral geographic ranges in islands: two developed for character-state reconstruction that allow only single-island ranges and do not explicitly associate speciation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
137
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(141 citation statements)
references
References 50 publications
3
137
1
Order By: Relevance
“…Because of the uniformity in habitat across a broad and diverse region, it does not appear that Pacific Cyrtandra radiated in response to ecological pressures (Cronk et al, 2005). Rather, the genus more likely diverged under a classic dispersal-mediated allopatry model (sensu Clark et al, 2008). Most species within Cyrtandra are narrowly distributed endemics occupying no more than a single archipelago, a single island or even a single valley, further supporting this hypothesis.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Because of the uniformity in habitat across a broad and diverse region, it does not appear that Pacific Cyrtandra radiated in response to ecological pressures (Cronk et al, 2005). Rather, the genus more likely diverged under a classic dispersal-mediated allopatry model (sensu Clark et al, 2008). Most species within Cyrtandra are narrowly distributed endemics occupying no more than a single archipelago, a single island or even a single valley, further supporting this hypothesis.…”
Section: Introductionmentioning
confidence: 94%
“…Previous divergence dating analysis has indicated that a large number of species have arisen over a relatively short time (Clark et al, 2008); a rapid species divergence resulting in potentially homoplastic character suites between lineages could be contributing to taxonomic issues in Cyrtandra.…”
Section: Taxonomymentioning
confidence: 99%
See 2 more Smart Citations
“…Dransfield 1981). Genera such as Cyrtandra (Gesneriaceae) colonized Oceania in a single event out of southeast Asia via Malesia, radiating extensively to produce numerous island endemics (Cronk et al 2005;Clark et al 2008). Similarly, drynaroid ferns possibly originated in southeast Asia and West Malesia, and then dispersed across Indonesia and the Philippines to New Guinea (Schneider et al 2008).…”
Section: Introductionmentioning
confidence: 99%